Thymoquinone and quercetin protect against hepatic steatosis in association with SIRT1/AMPK stimulation and regulation of autophagy, perilipin-2, and cytosolic lipases. (2nd January 2023) - Ashour, Hend; Rashed, Laila A.; Hassanein, Radwa T. M.; Aboulhoda, Basma E.; Ebrahim, Hasnaa A.; Elsayed, Mohamed H.; Elkordy, Miran A.; Abdelwahed, Omaima M.
Abstract: Background: We sought to investigate thymoquinone (TQ)/quercetin combination in preventing hepatic steatosis (HS). Materials and methods: The included rat groups; (1) Control, (2) HS model, (3) HS treated with TQ 10 mg.kg −1 .d −1, (4) HS treated with quercetin 50 mg.kg −1 .d −1, and (5) HS treated with both compounds for 4 weeks. Results: TQ/quercetin co-treatment augmented the anti-steatosis potential of each ingredient. The results revealed more ( p  < 0.001) sirtuin (SIRT1)/AMP-activated protein kinase (p-AMPK) upregulation compared to each treatment in line with autophagy protein Atg7 enhancement, and suppressed pro-inflammatory and oxidation markers. They diminished the hepatic lipogenic enzymes and perilipin-2 and activated the cytosolic lipases adipose triglyceride lipase (ATGL). Histological and Biochemical analysis revealed diminished lipid deposition and improved liver enzymes (alanine aminotransferase [ALT] and aspartate aminotransferase [AST]) compared to the data of separate treatments. Conclusion: TQ and quercitin effectively upregulated SIRT1/p-AMPK and regulated hepatic perilipin-2/ATGL, inflammation and oxidative stress, preserved liver structure and function. TQ/quercetin combination additively prevents HS.